A Case for Accelerating the Simultation Model Development Process: An Empirical Study - Yapa, S.T.W.S.; Clegg, D.R.; Perera, T.D.S. (My University, 2008)
It is noted through reading the literature on simulation project life cycle that model development is the most time consuming stage. The findings of the questionnaire survey administered among practitioners and academics also support the findings of the literature survey. Further, the questionnaire survey suggests that conceptual model development is the most difficult task in developing the simulation model. Therefore, it is suggested to conduct further research in developing a methodology to accelerate the simulation model development process in the line of improving the understanding between the user and the modeller.
Keywords: Simulation model development; Conceptual model